Variation of Concentrations of Angiotensin II, AngiotensinConverting Enzyme and Matrix Metalloprotease-9 in Tears and Serum of Patients with Diabetic Retinopathy - V. V. Neroev; N. B. Chesnokova; T. A. Pavlenko; T. D. Okhotsimskaya; O. V. Beznos; V. A. Fadeeva; S. V. Struchkova (Oftalʹmologiâ)
Diabetic retinopathy (DR) is becoming more and more widespread disease. Investigation of local changes of metabolic pathways in the eye improves our knowledge about diabetic retinopathy pathogenesis and provide perspective for the development of new pathogenetically based and individually focused therapy of this disease.Purpose of the study was to determine the concentrations of angiotensin II (AII), angiotensin-converting enzyme (ACE) and matrix metalloprotease-9 (MMP-9) in tears and serum of patients with diabetic retinopathy, estimate their significance for the evaluation of diabetic retinopathy severity and choice of treatment.Patients and methods. Tear and serum samples from 31 patients with diabetic retinopathy were analysed. Control group consisted of healthy volunteers of the same sex and age. Concentrations of angiotensin II, angiotensin-converting enzyme and matrix metalloprotease-9 were measured using the ELISA kits.Results: in controls angiotensin II concentration was 9.8 ± 5.5 pg/ml, in tears — 11.8 ± 6.6 pg/ml, angiotensin-converting enzyme concentration in serum was 82.6 ± 10.9 ng/ml, in tears it was 40 times lower: 2.5 ± 0.5 ng/ml, matrix metalloprotease-9 concentration in serum was 186.3 ± 8.9 ng/ml while in tears it was 100 times lower: 2.0 ± 0.9 ng/ml. In tears of patients with diabetic retinopathy levels of all 3 substances were significantly higher than in controls. Concentration of angiotensin II was 8 times higher, angiotensin-converting enzyme concentration 5 times higher and matrix metalloprotease-9 level 3 times higher. In serum angiotensin II concentration was increased 9 times, angiotensin-converting enzyme — 2 times. No difference in serum matrix metalloprotease-9 levels was observed. Thus diabetic retinopathy cause a significant activation of local and systemic rennin-angiotensin system. Local changes are more marked than systemic. Estimation of angiotensin II, angiotensin-converting enzyme and matrix metalloprotease-9 concentrations in tears can serve as an objective test for the diabetic retinopathy diagnostic and a pathogenetic rationale for the development of a new method of therapy — topical use of angiotensin-converting enzyme inhibitors.